2021
DOI: 10.3390/genes12020217
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Association Analyses of Fertility Traits in Beef Heifers

Abstract: The ability of livestock to reproduce efficiently is critical to the sustainability of animal agriculture. Antral follicle count (AFC) and reproductive tract scores (RTS) can be used to estimate fertility in beef heifers, but the genetic mechanisms influencing variation in these measures are not well understood. Two genome-wide association studies (GWAS) were conducted to identify the significant loci associated with these traits. In total, 293 crossbred beef heifers were genotyped on the Bovine GGP 50K chip a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 62 publications
0
13
0
Order By: Relevance
“…This SNP lies within NLGN4X, a neuronal cell surface protein with links to autism and Asperger syndrome. None of the regions identified in the current study overlap with other AFC GWAS results, although only literature reports for beef (Stegemiller et al, 2021) or Nellore cattle could be found (Oliveira Júnior et al, 2019;Grigoletto et al, 2020). The potential of a genomic marker for AFC is useful, as measuring AFC is time consuming and difficult in a nonresearch capacity.…”
Section: Discussionmentioning
confidence: 48%
See 1 more Smart Citation
“…This SNP lies within NLGN4X, a neuronal cell surface protein with links to autism and Asperger syndrome. None of the regions identified in the current study overlap with other AFC GWAS results, although only literature reports for beef (Stegemiller et al, 2021) or Nellore cattle could be found (Oliveira Júnior et al, 2019;Grigoletto et al, 2020). The potential of a genomic marker for AFC is useful, as measuring AFC is time consuming and difficult in a nonresearch capacity.…”
Section: Discussionmentioning
confidence: 48%
“…Determination of pathways involved may highlight key networks of genes influencing fertility and prenatal reproductive development. Genetic variation has been identified that is associated with AFC in beef heifers on chromosomes 2, 3, and 23 (Stegemiller et al, 2021). In Nellore cattle, regions of interest included chromosomes 1 and 26, which accounted for 6.2 and 7.3% of the total additive genetic variance, respectively (Grigoletto et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…After filtering, 575,053 genotypes from 22 animals were used for association analysis conducted in PLINK [45] using Fisher’s exact test. Locus association was inferred at alpha = 1×10 -5 , as reported by The Wellcome Trust Case Control Consortium [56] for case-control studies and previous GWAS analyses of reproductive traits in cows or heifers [4, 25, 32].…”
Section: Methodsmentioning
confidence: 99%
“…Another potential avenue for the identification of infertile heifers is the use of molecular phenotyping [24]. The pioneering efforts focused on genome-wide association studies (GWAS) to identify genetic markers associated with heifer fertility [4,12,[25][26][27][28][29][30][31][32][33][34][35][36][37][38], but only a few seem to be reproducible across populations [37]. More recent efforts have also focused on transcriptome [39][40][41] and metabolome [42] datasets characterizing these molecules in blood samples.…”
Section: Introductionmentioning
confidence: 99%
“…Speidel et al found some quantitative traits loci (QTL) that are presumed to be associated with heifer pregnancy and stayability [38]. Some additional fertility traits that have been studied include antral follicular count (AFC) and reproductive tract score (RTS), with a sample size of 293 heifers [39]. Even though all those studies were able to find some loci and candidate genes associated with reproduction, the researchers concluded that validation studies were needed as they were not sure about the results.…”
Section: Previously Studied Reproductive Traits At the Genetic Levelmentioning
confidence: 99%